Living teacher education in Hawaiʻi : critical perspectives - Twomey, Sarah Jane, 1964-; Johnson, Richard T., 1956- (University of Hawaiʻi Press, 2019)
He 'a'ali'i kū makani mai au, 'a'ohe makani nāna e kula'i.I am the wind withstanding 'a'ali'i. No gale can push me over.--Mary Kawena Pukui, 'Ōlelo No'eau: Hawaiian Proverbs and Poetical SayingsThese stories talk back to hegemonic education systems of United States reform that may seem insurmountable. Like the humble 'a'ali'i withstanding the wind, these scholarly endeavors stand as examples of how small, lived stories can have profound influence in the face of dominant knowledge systems.--Eōmailani KukahikoWorking across diverse research boundaries, Living Teacher Education in Hawai'i: Critical Perspectives shares teacher education narratives analyzed through embodied and postcolonial approaches to educational research. Each of the six essays offers meaningful application to educational contexts by provoking counternarratives that inspire new paradigms for teacher learning and research. The contributors analyze vivid cases of their own daily classroom and school-wide experiences as examples that give insight into current issues in teacher education in Hawai'i, including Indigenous methods and pedagogy; autoethnographic approaches for studying teacher experience; multilingual paradigms for teacher training; performative inquiry in becoming a teacher; women as leaders in education; and Native Hawaiian drama-driven storytelling as lived curriculum. This set of essays gives evidence of how critical engagement and lively writing do not have to be mutually exclusive. Laced with the powerful voices and perspectives of experienced teacher educators who are wise, creative, and critical in their grasp of current teacher education practices around the country, Living Teacher Education in Hawai'i should be read by teachers and teacher educators who dedicate their lives to grappling with the challenges of practicing social justice in diverse educational communities.